2021
DOI: 10.1080/02664763.2021.1911966
|View full text |Cite
|
Sign up to set email alerts
|

Confounding adjustment methods for multi-level treatment comparisons under lack of positivity and unknown model specification

Abstract: Imbalances in covariates between treatment groups are frequent in observational studies and can lead to biased comparisons. Various adjustment methods can be employed to correct these biases in the context of multi-level treatments ( > 2). Analytical challenges, such as positivity violations and incorrect model specification due to unknown functional relationships between covariates and treatment or outcome, may affect their ability to yield unbiased results. Such challenges were expected in a comparison of fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…During our stepwise regression analyses using the likelihood ratio test, however, the sex variable was removed from the final multivariable regression models of both SM and WB. This is likely due to unknown functional relationships between sex and other independent variables, when explaining SM and WB occurrence [59]. Aguirre et al [31] also reported that sex was not a significant variable for breast myopathies, although raw frequency indicated that male broilers had more frequently WB and WS.…”
Section: Plos Onementioning
confidence: 99%
“…During our stepwise regression analyses using the likelihood ratio test, however, the sex variable was removed from the final multivariable regression models of both SM and WB. This is likely due to unknown functional relationships between sex and other independent variables, when explaining SM and WB occurrence [59]. Aguirre et al [31] also reported that sex was not a significant variable for breast myopathies, although raw frequency indicated that male broilers had more frequently WB and WS.…”
Section: Plos Onementioning
confidence: 99%
“… 29 Arona Diop and colleagues stated that the robust variance estimator used with OW is conservative. 30 Reifeis and Hudgens examined the performance of the robust variance estimator when used with ATT weights and found that the estimator may be either conservative or anticonservative, concluding that the resultant confidence intervals will not be valid. 31 We are unaware of the previous similar results for MW.…”
Section: Discussionmentioning
confidence: 99%
“…To adjust for confounding (age, sex, comorbidities (the age adjusted Charlson index), number of regular medications and vital signs as proxies for severity of illness), we used an overlap weights approach, wherein each individual receives a weight that is proportional to the inverse of their probability to choose a particular setting [23]. Confidence intervals were obtained using a robust variance estimator [24].…”
Section: Discussionmentioning
confidence: 99%